2012
DOI: 10.1089/jmf.2011.0145
|View full text |Cite
|
Sign up to set email alerts
|

Bromelain-Induced Apoptosis in GI-101A Breast Cancer Cells

Abstract: Bromelain is a proteolytic enzyme extracted from the stems and the immature fruits of pineapple that was found to be antitumorigenic in different in vitro models. Bromelain has been reported to promote apoptosis, particularly in breast cancer cells, with the up-regulation of c-Jun N-terminal kinase and p38 kinase. Our study was designed to determine if bromelain could induce apoptosis in GI-101A breast cancer cells. GI-101A cells were treated with increasing concentrations of bromelain for 24 hours. The effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
30
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 22 publications
7
30
0
2
Order By: Relevance
“…In contrast, the inhibitory effects of bromelain are dependent on its proteolytic activity, which allow it to remove certain cell surface molecules associated with cellular migration and adherence [27]. The proteolytic activity of bromelain has also been reported to promote apoptosis in a number of human cancer cells, particularly in breast cancer cells [18, 28]. …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the inhibitory effects of bromelain are dependent on its proteolytic activity, which allow it to remove certain cell surface molecules associated with cellular migration and adherence [27]. The proteolytic activity of bromelain has also been reported to promote apoptosis in a number of human cancer cells, particularly in breast cancer cells [18, 28]. …”
Section: Discussionmentioning
confidence: 99%
“…Anticancer properties of bromelain or NAC, individually, have been evaluated in some in vitro and in vivo models before. Bromelain has shown cytotoxic and/or cytostatic effects on murine lung carcinoma, mammary adenocarcinoma, leukemia, lymphoma, sarcoma, melanoma and ascitic tumor cell lines [23][24][25][26], as well as on human cell lines derived from gastric and colon carcinoma [23,27,28], glioma [29], breast cancer [30][31][32], epidermoid carcinoma, melanoma [33] and malignant peritoneal mesothelioma [34]. Bromelain was also found to induce differentiation of leukemia cell lines in vitro [35] and to exert chemopreventive effects on skin [36][37][38] and colon [28] tumorigenesis in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Dhandayuthapani et al confirmed the dose‐dependent cytotoxic effects of bromelain in the GI‐101A breast cancer cell line. Bromelain was found to increase the level of caspase‐cleaved cytokeratin (CK18), one of the markers indicating cell death via apoptosis.…”
Section: Applicationsmentioning
confidence: 91%